The Media of the Descent of Jesus, peace be upon him, by Imam Abd al-Rahman bin Abi Bakr Jalal al-Din al-Suyuti, who died (year 911 AH) - study and investigation - (Islamic Sciences Journal, 2023)
The author has scribed the descent of Jesus (peace be upon him) in the last days of the world, and that he will govern according the laws of our Prophet Muhammad (peace be upon him), and he preached his nation about the coming of the Prophet Muhammad (peace be upon him), and he will look to the Quran  and will  understand all provisions relating to Islamic law without the need to review the Sunnah, He will rule in the money funds unlike what exists now, which means that  he will rul as it is ruled by the Prophet (peace be upon him). Jesus will come after Al- Mahdi, Al-Mamahdi and fills the earth with justice as it is filled injustice then  Jesus will come and support  the creation of Al-Mahdi. Then the author mention  the meeing between Jesus and the Prophet Muhammad (peace and blessing upon them) and support this subject with many evidences, including the dignity of the ascetic to see the Prophet vigilant. he will reveal to him by Gabriel (peace be upon him), and then the descent of Gabriel to the earth after the death of the Prophet (peace be upon him) which, contrdicts to what some people are saying that Gabriel is not coming off after the death of the Prophet (peace be upon him). The author  ended his book that Jesus will pray behind Al-Mahdi .